Ponds as insect chimneys: Restoring overgrown farmland ponds benefits birds through elevated productivity of emerging aquatic insects. (January 2020) - Lewis-Phillips, Jonathan; Brooks, Stephen J.; Sayer, Carl Derek; Patmore, Ian R.; Hilton, Geoff M.; Harrison, Anne; Robson, Hannah; Axmacher, Jan C.
Highlights: Farmland pond management strongly enhances emergent insect communities. Emergent insects abundance increases 18 times following pond management. Pond management leads to a 25-times increase in emergent insect biomass. Day-to-day fluctuations in water temperature can predict insect emergences. Local farmland bird communities are linked to emergent pond insect abundance. Abstract: Farmland bird populations have experienced severe declines across Europe and elsewhere. Agricultural intensification is believed to be a main factor behind these declines, with losses of non-cropped features, such as farmland ponds, identified as a key driver. Since the 1950s, many European farmland ponds have been in-filled or, through lack of management, become terrestrialised. Restoring terrestrialised farmland ponds has been shown to significantly increase the abundance and diversity of local farmland bird communities. It has been hypothesised that farmland birds are specifically attracted to open-canopy ponds due to increased emergent aquatic insect availability, but this link has hitherto been little explored. This study investigates how farmland pond management influences emergent aquatic insects, and how emergent insect abundance and biomass is linked to local bird assemblages. Insect emergences showed an 18-fold higher abundance and a 25-fold higher biomass at managed open-canopy ponds in comparison to their unmanaged overgrown counterparts, with day-to-day fluctuations in pond water temperature a key predictor of insect emergences. Species richness and abundance of birds at farmland ponds were strongly positively linked to the abundance of emergent insects. Furthermore, insect emergence peaks occurred on different days in different restored ponds such that the pond landscape afforded extended feeding opportunities for birds. Our findings suggest that restoring networks of terrestrialised farmland ponds to open-canopy macrophyte-dominated conditions could be a highly effective way of increasing the availability of aquatic insect prey for birds. This study highlights an urgent need to re-evaluate pond restoration and management within agri-environmental schemes in Europe and beyond.